Creative vs Defective: A Critical Review of Malang Creative Center (MCC) in Malang City - Ineru, Bunga Pasadena; Yusran, Yusfan Adeputera; Santoso, Joko Triwinarto; Wijaya, Moch. Ardiansyah Fendy; Kusdiwanggo, Susilo (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2024)
The Malang Creative Center (MCC) construction is a step taken by the Malang City government to support the flow of modernization and as a forum for Malang residents to develop their creativity. The MCC display concept is planned by combining the shape of the temple and the unique cultural background of Malangan. However, during the development process, many changes were different from the initial concept. All these things make this building interesting to study critically. Therefore, this study aims to critically identify these changes in the idea as well as rectify the perceptions that have developed. Descriptive analysis was carried out through direct observation of objects by describing real conditions and explanatory verification of the results of these observations with visitors' views via a questionnaire. The analysis results show that the public's perception of the visual MCC has a good level of compatibility with the concept and function of the building, although some aspects still require attention regarding the visitor’s safety and comfort.